Thyroid Cancer Incidence Trends Among Filipinos in the United States. (15th December 2021) - Megwalu, Uchechukwu C.; Osazuwa‐Peters, Nosayaba; Moon, Peter; Palaniappan, Latha P.
Abstract : Objective: To analyze thyroid cancer incidence trends among Filipinos relative to non‐Filipino Asians and non‐Hispanic Whites in the US. Study Design: Population‐based analysis of cancer incidence data. Methods: Population‐based analysis of cancer incidence data from Surveillance, Epidemiology, and End Results 9 detailed Asian/Pacific Islander subgroup incidence and population datasets. Adult patients aged 20 and older with thyroid cancer diagnosed in 2004 to 2014 were included. Annual percent change (APC) of the incidence rates were calculated using joinpoint regression analysis. Results: The incidence rates were 19.57 (95% CI 19.03–20.12) per 100, 000 for Filipinos, 10.45 (95% CI 10.22–10.68) per 100, 000 for non‐Filipino Asians, and 13.94 (95% CI 13.85–14.02) per 100, 000 for non‐Hispanic Whites. The highest increase was seen among non‐Hispanic Whites (average APC 5.04, 95% CI 4.61–5.46). Incidence rates of tumors ≤ 2 cm remained stable among Filipinos but increased in non‐Filipino Asians (average APC 5.38, 95% CI 2.51–8.34) and non‐Hispanic Whites (average APC 5.81 95% CI 4.52–7.11). Conclusion: Filipinos have high incidence of thyroid cancer compared with other racial/ethnic groups. However, non‐Hispanic Whites have the highest increase in incidence rates, resulting in a significant narrowing of the gap in incidence rates between Filipinos and non‐Hispanic Whites. This is most likely due to enhanced detection of small tumors in non‐Hispanic Whites. Laryngoscope, 132:1495–1502, 2022